2016
DOI: 10.1002/ange.201606707
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Hydride Transfer as a Decisive Mechanistic Step in the Reactions of the Unligated Gold Carbide [AuC]+ with Methane under Ambient Conditions

Abstract: The reactivity of the cationic gold carbide [AuC]+ (bearing an electrophilic carbon atom) towards methane has been studied using Fourier transform ion cyclotron resonance mass spectrometry (FT‐ICR‐MS). The product pairs generated, that is, Au+/C2H4, [Au(C2H2)]+/H2, and [C2H3]+/AuH, point to the breaking and making of C−H, C−C, and H−H bonds under single‐collision conditions. The mechanisms of these rather efficient reactions have been elucidated by high‐level quantum‐chemical calculations. As a major result, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…At present, researchers are concerned about the reactions of methane with metal ions such as Os + [ 11 ], Pt + [ 12 ], Ta + [ 13 ] and Rh(0) [ 14 ] and metal oxides such as MgO + [ 15 ], PbO + [ 16 ], V 4 O 10 + [ 17 ] and Re 2 O 7 + [ 18 ]. In addition to metal ions and their oxides, studies have shown that metal carbides can also activate methane, such as FeC 6 − [ 19 ], Mo 2 C 2 − [ 20 ], Ta 2 C 4 − [ 21 ], FeC 3 − [ 6 ], AuC + [ 22 ], FeC 4 + [ 23 ] and M C + [ 7 ]. These studies have explored some possible mechanisms for the activation of methane by metal carbide clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, researchers are concerned about the reactions of methane with metal ions such as Os + [ 11 ], Pt + [ 12 ], Ta + [ 13 ] and Rh(0) [ 14 ] and metal oxides such as MgO + [ 15 ], PbO + [ 16 ], V 4 O 10 + [ 17 ] and Re 2 O 7 + [ 18 ]. In addition to metal ions and their oxides, studies have shown that metal carbides can also activate methane, such as FeC 6 − [ 19 ], Mo 2 C 2 − [ 20 ], Ta 2 C 4 − [ 21 ], FeC 3 − [ 6 ], AuC + [ 22 ], FeC 4 + [ 23 ] and M C + [ 7 ]. These studies have explored some possible mechanisms for the activation of methane by metal carbide clusters.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have explored some possible mechanisms for the activation of methane by metal carbide clusters. For example, the study of AuC + reveals a special hydride-transfer mechanism (HT) [ 22 ], while the study of FeC 3 - shows that methane and atomic clusters generate CC-coupling reaction products at high temperatures and explained the possible mechanism of non-oxidized methane aromatization at the molecular level [ 6 ]. The study of FeC 4 + shows that the cluster can activate the C–H bonds of methane via the hydrogen-atom transfer (HAT) mechanism at ambient temperature; the study used the frontier orbital theory to explain the root cause of the HAT reaction [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…20 Interestingly, the adsorbed oxygen species on metal surfaces were demonstrated to exhibit promotional or inhibitory effects, which depends strongly on the nature of metals. [21][22][23][24][25][26] In more recent years, a series of mechanistic scenarios were explored by Schwarz et al, [13][14][15][16][27][28][29] in which the classical hydrogen-atom transfer (HAT), 27 protoncoupled electron transfer (PCET), 28 and hydride transfer (HT) 29 pathways were explored and distinguished in various reaction systems for methane C-H activation.…”
Section: Introductionmentioning
confidence: 99%
“…7−15 In the cases of transition metal carbide clusters, it was found that the center for activation of C−H bonds of methane can be either the transition metal 16,17 or the carbon atoms. 18,19 Also, reactivity of vanadium-doped rhodium clusters toward C−H activation were investigated with density functional theory. 14 The results showed that, as compared to the pure rhodium clusters, the monovanadiumdoped rhodium clusters have higher reactivity toward C−H activation.…”
Section: Introductionmentioning
confidence: 99%